A case study of Mauritius and South Africa: an analysis of good governance and human capital on export diversification - Pamachete, Rumbidzai Sylviah (My University, 2018)
This paper looks at how human capital and good governance interact with export diversification in an economy, with particular reference to Mauritius and South Africa. Further, a comparative analysis is done on how the degree of human capital development and good governance determines the level of export concentration. Findings show that there is a positive correlation between human capital and good governance on the one hand, and export diversification on the other. The comparative analysis showed that the more developed human capital and governance are in a country, the less concentrated exports become. Recommendations are suggested for policy makers on how to manage the two determining factors with a view to expanding export diversification and ultimately growing economies.
A research report submitted In accordance to Master of Commerce in Economics (CH0017): weighted at 50% of the Masters’ program. School of Economics and Business Sciences, University of Witwatersrand.
Keywords: Human capital; Exporting